2015
DOI: 10.4018/978-1-4666-7373-1.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Program for Management and Treatment of Stress Urinary Incontinence in Women

Abstract: Stress Urinary Incontinence (SUI), defined as involuntary urine leakage caused by physical activity and/or efforts, is a frequently found pathology among women that significantly affects their quality of life. SUI treatments are often less effective than expected because they require a conscious effort by the patient to follow them correctly and usually have drawbacks, such as their high cost, time, and/or schedule requirements. ICT-mediated Physical Therapy treatment programs can be useful to improve Stress U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Just over 40% (12/28, 43%) of these were solely mobile apps, 4% (1/28) trialed a smartphone-based messaging system, 11% (3/28) were internet-based programs, and 7% (2/28) were dedicated to videoconferencing. A total of 32% (9/28) of the technologies involved the use of a portable vaginal biofeedback or accelerometer-based device [ 36 - 38 , 43 , 44 , 48 , 49 , 53 , 54 , 62 , 67 ,​ 71 , 76 ] that provided real-time feedback transmitted via Bluetooth to a mobile app or, in one instance, to a computer application [ 43 ]. In addition to the vaginal device, electromyographic data were integrated from surface electrodes attached to the abdominal muscles [ 37 , 38 ] or PFMs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Just over 40% (12/28, 43%) of these were solely mobile apps, 4% (1/28) trialed a smartphone-based messaging system, 11% (3/28) were internet-based programs, and 7% (2/28) were dedicated to videoconferencing. A total of 32% (9/28) of the technologies involved the use of a portable vaginal biofeedback or accelerometer-based device [ 36 - 38 , 43 , 44 , 48 , 49 , 53 , 54 , 62 , 67 ,​ 71 , 76 ] that provided real-time feedback transmitted via Bluetooth to a mobile app or, in one instance, to a computer application [ 43 ]. In addition to the vaginal device, electromyographic data were integrated from surface electrodes attached to the abdominal muscles [ 37 , 38 ] or PFMs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 10% (4/41) of the studies, women also attended supervised group sessions once a week to undertake PFMT via teleconferencing [ 59 ], in person [ 52 , 57 ] with a maximum of 4 women per group [ 52 ], or specific to one of the study arms (app plus physiotherapy group) [ 57 ]. In the study by Pla et al [ 49 ], Skype was the medium for supervision of group-based hypopressive abdominal exercises 3 times per week (5-9 women per group), with women also receiving monthly individual videoconferencing sessions to check progress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just over 40% (12/28, 43%) of these were solely mobile apps, 4% (1/28) trialed a smartphone-based messaging system, 11% (3/28) were internet-based programs, and 7% (2/28) were dedicated to videoconferencing. A total of 32% (9/28) of the technologies involved the use of a portable vaginal biofeedback or accelerometer-based device [36][37][38]43,44,48,49,53,54,62,67,71,76] that provided real-time feedback transmitted via Bluetooth to a mobile app or, in one instance, to a computer application [43]. In addition to the vaginal device, electromyographic data were integrated from surface electrodes attached to the abdominal muscles [37,38] or PFMs [36].…”
Section: Types Of Dts (Consensus On Exercise Reporting Template For P...mentioning
confidence: 99%
“…Confirmation of a voluntary PFM contraction was undertaken in just under half (19/41, 46%) of the studies and was either not included in the study design in 41% (17/41) of the studies or not indicated or appropriate (5/41, 12%). Confirmation was obtained through digital assessment [39,57,61,69], which was also used to teach a correct contraction or relaxation of the PFM [52,67]; biofeedback or the digital device [36][37][38]43,44,49,62]; or a combination of both [42,47,51,59,71,76]. Digital assessment was undertaken by a specialized HCP, although it was not indicated who performed this procedure in 7% (3/41) of the studies [51,57,71].…”
Section: Content Of Pfmt (Consensus On Exercise Reporting Template Fo...mentioning
confidence: 99%